Cytotoxic Deoxypodophyllotoxin Can Be Extracted in High Purity from Anthriscus sylvestris Roots by Supercritical Carbon Dioxide - Seegers, Christel L. C.; Tepper, Pieter G.; Setroikromo, Rita; Quax, Wim J. (Planta Medica, 2018)
Deoxypodophyllotoxin is present in the roots of Anthriscus sylvestris. This compound is cytotoxic on its own, but it can also be converted into podophyllotoxin, which is in high demand as a precursor for the important anticancer drugs etoposide and teniposide. In this study, deoxypodophyllotoxin is extracted from A. sylvestris roots by supercritical carbon dioxide extraction. The process is simple and scalable. The supercritical carbon dioxide method extracts 75 – 80% of the total deoxypodophyllotoxin content, which is comparable to a single extraction by traditional Soxhlet. However, less polar components are extracted. The activity of the supercritical carbon dioxide extract containing deoxypodophyllotoxin was assessed by demonstrating that the extract arrests A549 and HeLa cells in the G2/M phase of the cell cycle. We conclude that biologically active deoxypodophyllotoxin can be extracted from A. sylvestris by supercritical carbon dioxide extraction. The method is solvent free and more sustainable compared to traditional methods.
Keywords: Anthriscus sylvestris; Apiaceae; deoxypodophyllotoxin; etoposide; supercritical carbon dioxide extraction